2009
DOI: 10.1016/j.joca.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Defining the load bearing axis of the lower extremity obtained from anterior-posterior digital radiographs of the whole limb in stance

Abstract: Our computer-assisted method was reproducible, and should be considered an alternative method for the measurement of the alignment of the whole leg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Multiple studies found computer-based measurements to have good to excellent reliability equal to traditional measurements in a variety of orthopaedic measurements, including the Cobb angle in adolescent idiopathic scoliosis, 1,2,8 templating in cementless total hip arthroplasty, 13 long leg radiographs for leg length evaluation, 3 hallux valgus deformity angles, 4 knee joint alignment in adult patients, 14 and determination of the metaphyseal-diaphyseal angle in tibia vara patients. 6 One of the major challenges in comparing the results of these studies is the lack of a single computer-based measurement program to allow standardization in measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Multiple studies found computer-based measurements to have good to excellent reliability equal to traditional measurements in a variety of orthopaedic measurements, including the Cobb angle in adolescent idiopathic scoliosis, 1,2,8 templating in cementless total hip arthroplasty, 13 long leg radiographs for leg length evaluation, 3 hallux valgus deformity angles, 4 knee joint alignment in adult patients, 14 and determination of the metaphyseal-diaphyseal angle in tibia vara patients. 6 One of the major challenges in comparing the results of these studies is the lack of a single computer-based measurement program to allow standardization in measurements.…”
Section: Discussionmentioning
confidence: 99%
“…10 We used the guidelines of Portney and Watkins 11 to assess reliability, which are stricter criteria than those used in many papers evaluating similar digital radiographic measurements. 1,2,15 These studies used different reliability criteria, and if these had been employed in the current study, the reliability would have been good to excellent. The stricter criteria were chosen for evaluation given the strength of reliability found for standard radiographs by Gordon et al 10 We did observe 2 specific errors with the computerbased measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In 2D studies, Iseki et al [3] evaluated the reliability of the inter-and intra-observer assessments of the mechanical alignment. Sailer et al [18] assessed the axial alignment and joint angulations of the lower extremity using mechanical axis measurements on the conventional and digital radiographs.…”
Section: Related Workmentioning
confidence: 99%
“…2 θ is the angle between the femur mechanical axis and the tibia mechanical axis. 3 θ is the angle between the femur mechanical axis and the knee transverse axis. 4 θ is the angle between the knee transverse axis and the tibia mechanical axis.…”
Section: Special Featuresmentioning
confidence: 99%
See 1 more Smart Citation